Mainstreaming gender dimensions in water management for food security and food safety - Chimonidou D.; Pitta C.; Vassiliou L. (Mainstreaming gender dimensions in water management for food security and food safety, 2007)
In Cyprus, women working in agriculture comprise 3 percent of the working population of the country and are mainly involved in the growing of field crops and livestock rearing. Family farm is the typical production unit in Cypriot agriculture, with the farm family being the main labour source. Rural women account for 16,5 percent of the total population and constitute substantial and integral part of the country's labour force. Women have a significant role to play and the need to support and raise women's profile in the decision-making process is clear. Throughout the twentieth century, there has been an increasing trend towards the use of stored and processed foods. Initially, this was a response to industrialisation and the need to provide food for large number of people living in cities. More recently, the consumer has come to expect access to a wide variety of foodstuffs throughout the year, without the restrictions imposed by seasonal and regional availability and there is increasing reliance on convenience and fast foods. The processes involved in producing and storing foods frequently require the addition of chemicals (either natural or man-made) to improve the safety or to preserve the nutritional quality. An additional benefit is increased palatability and attractiveness of foodstuffs to the consumer. Clearly the safety of such chemicals has to be assured and their use controlled in order to avoid harmful effects.
2. Regional Coordination Workshop of GEWAMED (Mainstreaming Gender Dimensions into Water Resources Development and Management in the Mediterranean Region), 2007/03/12-14, Larnaca (Cyprus)